The Effect of Birth Ball Use on Labor Progress: A Literature Review - Harwin Holilah Desyanti; Shofiatul Widad (Syntax Corporation Indonesia, 2023)
The problem of the high number of MMR and IMR in Indonesia is that there are still many prolonged labor which is one of the several causes of maternal and newborn mortality. One of the therapies that can be done to prevent this is the use of Birth balls. Birth balls can prevent maternal fatigue caused by long duration of labor. The purpose of this articel was to provide an overview of the effect of birth ball exercises on the progress of the first stage of labor. This research used the Literature Review method. The sampling method used purposive sampling technique by selecting articles with appropriate topics. The results of the study through the stages of identification, screening, eligibility and include, found that there was an effect of giving birth ball exercises therapy in accelerating the progress of labor in maternity mothers. This is because the birth ball exercise is able to relieve pressure and increase the area of the pelvis, encourage the baby's head to descend, help uterine contractions more effectively, accelerate cervical dilation, and help to relax the ligaments in the pelvis.